Tertiary Prevention Behavior among Elderly with Hypertension Based on the Information Motivation Behavioral Skill Model - Dewi Laraswati; Argyo Demartoto; Ika Sumiyarsi Sukamto; Erindra Budi Cahyanto; Haryani Saptaningtyas (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Hypertension among the elderly is a prevalent health problem with a high risk of serious complications, including stroke and renal failure. However, tertiary prevention behaviors, such as treatment adherence and lifestyle management, remain suboptimal. The Information Motivation Behavioral Skill (IMB) model suggests that health behavior is influenced by information, motivation, and behavioral skills. This study aimed to analyze tertiary prevention behavior among elderly patients with hypertension based on the IMB model. Subjects and Method: This was an analytic observational study with a cross-sectional design. A total of 252 older people with hypertension were selected using simple random sampling at Gambirsari and Sibela Primary Health Centers in Surakarta, Central Java, Indonesia. Variables independent were information, motivation, behavioral skills, and the dependent was tertiary prevention behavior. Data were collected using questionnaires and analyzed using path analysis run on STATA 13. Results: Information (b=4.32; 95% CI=2.2 to 6.43; p<0.001), motivation (b=3.15; 95% CI=1.77 to 4.54; p<0.001), and behavioral skills (b=3.33; 95% CI=2.09–4.57; p<0.001) had significant direct effects on tertiary prevention behavior. Indirect effects through behavioral skills were also observed for information (b=0.81; 95% CI=0.19 to 1.42; p=0.010) and motivation (b=1.49; 95% CI= 0.88 to 1.11; p<0.001), with AIC = 401.34, BIC = 426.05. Conclusion: Information, motivation, and behavioral skills directly influence tertiary prevention behavior among elderly patients with hypertension. In addition, information and motivation also have indirect effects through behavioral skills.